Supply Chain Management practices in the electro-electronics sector in Brazil: Evolutionary approach, information technology adoption and management actions - De Sousa Jabbour, Ana Beatriz Lopes [UNESP]; Alves Filho, Alceu Gomes; Noronha Viana, Adriana Backx; Chiappetta Jabbour, Charbel José [UNESP] (Inderscience Publishers, 2012)
This paper examines the current level of adoption of Supply Chain Management (SCM) practices in the electro-electronic sector in Brazil and aims to identify the management and Information Technology (IT) actions that have been implemented to support the adoption of those practices. An e-mail survey was conducted. Descriptive statistics techniques were employed for data analysis. This study makes contributions to the electro-electronics sector and to the topics related to SCM, such as identifi cation and level of adoption of SCM practices. Another contribution of this research is the investigation of whether approaches such as Enterprise Resources Planning (ERP), Workshop with Customers, Electronic Data Interchange (EDI), Workshop with Suppliers and electronic Kanban are commonly used to support SCM practices. So far, this is the fi rst research on SCM practices in the electro-electronics sector in Brazil. Copyright © 2012 Inderscience Enterprises Ltd.
Keywords: Brazil; Electro-electronics sector; Information technology; Management actions; Supply chain management practices; Chain management; Current levels; Descriptive statistics; Electronic kanban; Enterprise resources planning; Evolutionary approach; Information technology adoption; Electronic data interchange; Research; Supply chain management